Highly doped semiconductor plasmonic nanoantenna arrays for polarization selective broadband surface-enhanced infrared absorption spectroscopy of vanillin - Barho Franziska B.; Gonzalez-Posada Fernando; Milla Maria-Jose; Bomers Mario; Cerutti Laurent; Tournié Eric; Taliercio Thierry (Nanophotonics, 2017)
Tailored plasmonic nanoantennas are needed for diverse applications, among those sensing. Surface-enhanced infrared absorption (SEIRA) spectroscopy using adapted nanoantenna substrates is an efficient technique for the selective detection of molecules by their vibrational spectra, even in small quantity. Highly doped semiconductors have been proposed as innovative materials for plasmonics, especially for more flexibility concerning the targeted spectral range. Here, we report on rectangular-shaped, highly Si-doped InAsSb nanoantennas sustaining polarization switchable longitudinal and transverse plasmonic resonances in the mid-infrared. For small array periodicities, the highest reflectance intensity is obtained. Large periodicities can be used to combine localized surface plasmon resonances (SPR) with array resonances, as shown in electromagnetic calculations. The nanoantenna arrays can be efficiently used for broadband SEIRA spectroscopy, exploiting the spectral overlap between the large longitudinal or transverse plasmonic resonances and narrow infrared active absorption features of an analyte molecule. We demonstrate an increase of the vibrational line intensity up to a factor of 5.7 of infrared-active absorption features of vanillin in the fingerprint spectral region, yielding enhancement factors of three to four orders of magnitude. Moreover, an optimized readout for SPR sensing is proposed based on slightly overlapping longitudinal and transverse localized SPR.